Fabrication of Triethylenetetramine Terminal Hyperbranched Dendrimer-Like Polymer Modified Silica Gel and Its Prominent Recovery Toward Au (III) - Zhang, Ying; Qu, Rongjun; Xu, Ting; Zhang, Yu; Sun, Changmei; Ji, Chunnuan; Wang, Ying (Frontiers in Chemistry, 2019)
To further increase the quantity and density of functional groups on adsorbent, terminal triethylenetetramine hyperbranched dendrimer-like polymer modified silica-gel (SG-TETA and SG-TETA2) was synthesized. The hyperbranched dendrimer-like polymer was successfully introduced onto silica gel and new cavities were formed, which was demonstrated by FTIR, SEM, and BET. The highest adsorption capacities of SG-TETA and SG-TETA2 obtained from Langmuir model towards Au(III) were 2.11, and 2.27 mmol g-1, respectively, indicating that SG-TETA2 possessing more functional groups had better adsorption ability. Moreover, the adsorbents combined with Au(III) ion through chelation and electrostatic attraction mechanism, after which reduction reactions for Au(III) ion loaded on adsorbents proceeded. SG-TETA2 had better adsorption selectivity than SG-TETA in removing Au(III) in Au-existed ion solution systems. SG-TETA2 had higher overall adsorption capacities compared to silica-gel-based hyperbranched polymers functionalized by diethylenetriamine. Therefore, the effective recovery make SG-TETA2 a practical adsorbent in removing Au(III) ion from e-wastes and industrial effluents with much prospect.